2013
DOI: 10.1177/1534734613502043
|View full text |Cite
|
Sign up to set email alerts
|

Heel Ulcer and Blood Flow

Abstract: A young female diabetic patient is reported, who presented with a double foot lesion. She presented with a first metatarsal head exposure concomitant with a heel wet gangrene. Magnetic resonance demonstrated osteomyelitis of the rear portion of the calcaneus. Transmetatarsal amputation was performed and a wide debridement was required to remove all gangrenous tissue from the heel wound. The pedal artery was palpable; the posterior tibial pulse was present, but weak.Transcutaneous oximetry (TcPO2) at the dorsum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…These data imply some specific considerations: the restoration of the heel area or rearfoot is the main finding for achieving healing. 6,20 The involvement of BTA arteries (in this case, the plantar arch) is confirmed as a predictor of outcome regardless of ulcer location. 21,22 Peripheral revascularization is mandatory in patients with ischemic DFUs for allowing adequate restoration in the wound area 1,23 ; in the case of BTA-PAD, foot arteries should be revascularized (not only tibial arteries) to improve outcomes, using extreme revascularization techniques if required.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…These data imply some specific considerations: the restoration of the heel area or rearfoot is the main finding for achieving healing. 6,20 The involvement of BTA arteries (in this case, the plantar arch) is confirmed as a predictor of outcome regardless of ulcer location. 21,22 Peripheral revascularization is mandatory in patients with ischemic DFUs for allowing adequate restoration in the wound area 1,23 ; in the case of BTA-PAD, foot arteries should be revascularized (not only tibial arteries) to improve outcomes, using extreme revascularization techniques if required.…”
Section: Discussionmentioning
confidence: 65%
“…In relation to the variables influencing the outcomes of persons with heel DFUs, many factors have been found in previous similar studies: Örneholm et al 3 reported that nephropathy and edema were associated with poor outcome, whereas absence of chronic kidney disease was related to higher probability of healing 3 ; Chipchase et al 4 found that ulcer size (larger ulcers) and PAD were associated with worse outcome, whereas Bakheit et al 14 found that superficial ulcers and adequate foot perfusion were associated with higher probability of healing; Treiman et al 6 showed that normal renal function and patency of the posterior tibial artery below the ankle (BTA) were related to healing; Faglia et al 20 reported that the healing may be delayed or impaired in case of decreased blood flow in the heel region.…”
Section: Discussionmentioning
confidence: 99%
“…Разрешение ишемии конечности у таких больных, как правило, возможно, только при условии вос-становления прямого артериального кровотока к стопе по ПББА или ЗББА, поскольку МБА анатомически распо-ложена проксимальнее голеностопного сустава, а ее колла-теральные ветви на стопе развиты незначительно. Поэтому в случае язвенного дефекта пяточной области стопы пока-зана реканализация прежде всего ЗББА [35], в то время как акральные некрозы пальцев требуют восстановления кро-вотока по ПББА. Безусловно, клинические исходы эндо-васкулярной реваскуляризации у пациентов с СД и КИНК во многом зависят от ее своевременности.…”
Section: особенности эндоваскулярного лечения больных сд и кинкunclassified
“…4 Heel blood supply is equally compromised because it relies largely on collateral circulation from the posterior tibial artery. 3,5,6 Diseases, conditions, medications, or prolonged heel positioning without relief can cause ischemic changes to the heel's skin surface. 1,4 Risk Factors.…”
mentioning
confidence: 99%
“…The subcutaneous tissue is thin, highly vascularized, firm, and fibrous; it lacks muscle/fat tissue for cushioning/protection rendering it vulnerable to pressure and shear forces 4 . Heel blood supply is equally compromised because it relies largely on collateral circulation from the posterior tibial artery 3,5,6 . Diseases, conditions, medications, or prolonged heel positioning without relief can cause ischemic changes to the heel’s skin surface 1,4 …”
mentioning
confidence: 99%